Efektivitas Organisasi : Peran Pembagian Kerja dan Wewenang Melalui Kinerja Karyawan - Ramadani, Sah Putri (JaManKu: Jurnal Manajemen dan Kewirausahaan, 2025)
This study aims to determine whether the division of labor and delegation of authority partially affects employee performance. To find out whether the division of labor, delegation of authority and employee performance partially affects organizational effectiveness, to find out whether the division of labor and delegation of authority has an effect on organizational effectiveness through employee performance and delegation of authority. The total population in this study amounted to 114 people and 114 were sampled using a saturated sampling method, namely a sample that also represented the total population. The analysis technique used is path analysis. The results showed that the division of labor had no effect on employee performance, delegation of authority had a significant effect on employee performance, division of labor had no significant effect on organizational effectiveness, delegation of authority had no effect on organizational effectiveness, employee performance had a significant effect on organizational effectiveness, division of labor had no effect. on organizational effectiveness through employee performance with delegation of authority had a significant effect on organizational effectiveness through employee performance.